ANALISIS PENERIMAAN DAN PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DI MASA PANDEMI COVID-19 PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH (BPPRD) UPT PPD MEDAN UTARA - Suganda Suganda; Nurhayati Nurhayati (UNIVERSITAS DHARMAWANGSA, 2022)
Taxes are one of the government's greatest sources of revenue. The covid-19 pandemic was an infectious disease that spread evenly and simultaneously around the world at the end of 2019. The tax consists of two types: central and regional taxes. The tax on motorized vehicles is a tax on the ownership of ones that are included in the county tax. The research method in this study is mixed research with a descriptive approach. Research shows that at the time of the covid-19 pandemic, more direct than online, the covid-19 pandemic effect on the tax realized motor vehicles did not significantly affect the north pppp-field's tax office and the realization of the CKB is still said to be effective and contribute well, And the effort done is done more than optimal by performing some programs such as the relaxing payment program and the self-knocking program (PMKP).